Farm Size and Relative Economic Efficiency Of Seaweed Farming - Moch Prihatna Sobari (Buletin Ekonomi Perikanan, 1993)
The assessment is aimed at revealing the optimum level and farm efficiency of different sea weed farm sizes in Nusa Penida Bali. To come to these objectives, input-output relationship in sea weed production is exercised under Profit Function model. The study in indicates that most of sea weed farms in Nusa Penida have not yet realized optimum condition in production. Furthermore, most of them are under increasing return to scale. Also found in this study is the fact that medium farm size (251 - 500 m2) seem to be the most appropriate size giving the highest economic efficiency to the farmers. The policy implication for the sea weed farms being optimum are : (a) Technical improvement to optimize return to scale, and (b) price incentive to encourage sea weed farmers to develop.